HOLOCENE DEPOSITIONAL ENVIRONMENT CHANGE FROM MICROFOSSIL DATA OF DT1 CORE, MEKONG RIVER DELTA - Oanh, Ta Thi Kim; Lap, Nguyen Van (Vietnam Journal of Marine Science and Technology, 2007)
Holocene depositional environmental change in Dong Thap province, Mekong River Delta is reported on the base of microfossil data (diatom and foraminifera) from the boring core DT1. Totally 65 genera, 41 species of diatom, 27 benthic foraminifera genera (20 calcareous and 7 agglutinated genera) and 7 species are identified from the core samples. The stratigraphical changes of both diatom and foraminifera are usefitl to clarify Holocene sedimentmy environments. A successionfrom marsh/tidal flat sandy silt facies, sub-to intertidal flat to inner bay/prodelta mud facies suggests sea-level rising and datedfrom 11,285 to 7,090 ca.y.BP. Thesefacies changes related to sea-level changes, specially in early-middle Holocene, are the first discovery in the upper delta plain of the MRD.